A combined structural, microstructural and dilatometric analysis of MgPSZ. Issue 4 (April 2018) - Rondão, A.I.B.; Soares, M.R.; Tobaldi, D.M.; Ferreira, A.; Labrincha, J.A.; Marques, F.M.B.
Graphical abstract: Phase conversions and inherent dimensional changes in MgPSZ. Highlights: Combined structural, microstructural and dilatometric study of MgPSZ. Comparative analysis of XRD patterns using distinct software packages. Quantitative phase analysis by XRD using sintered bodies and powders. Quantitative phase analysis combining XRD and dilatometric data. Abstract: MgO-doped partially stabilized zirconia (MgPSZ) is a ceramic where three phases (cubic, tetragonal and monoclinic zirconia) might coexist due to non-equilibrium conditions and proper quantification of phase content is difficult. Here, a few selected compositions (in the 7–10 mol% MgO range) and firing profiles were studied in order to cover several phase compositions and microstructural features. An original attempt is made to correlate data obtained by X-ray diffraction (XRD), dilatometry (DIL) and scanning electron microscopy (SEM). Distinct software packages used in the analysis of XRD patterns of different samples confirmed the shortcomings of the assessment of phase content in sintered bodies while proper handling of DIL data provided complementary quantitative information on their phase content. The suggested procedure can be further used to obtain a subtle insight on phase development with temperature, subject of major relevance with respect to tuning of the mechano-thermal behavior of these ceramics.